Digital School: A Gateway to New Horizons for Developing the Teaching Profession in the Emirate of Sharjah - Alnaqbi, Anoud; Nashwan, Ayat (Al-Adab Journal, 2025)
The research aimed to identify the role of the digital school: a gateway to new horizons for developing the teaching profession in the Emirate of Sharjah. The descriptive analytical approach was used, and the results of the study concluded that the use of technology in education helps improve students’ performance in tests and academic studies, as the digital school can help reduce the educational gap between students with different needs, by providing customized educational experiences. The study recommended the need to prepare programs to prepare and train teachers to acquire the ethics and behaviors of digital citizenship and to employ digital educational resources to increase their awareness of the concepts of the digital school.